PLURALITAS AGAMA DAN KERUKUNAN UMAT BERAGAMA DI INDONESIA (Mencari Peran Pendidikan Agama di Perguruan Tinggi Umum) - Marzuki, Marzuki (Jurnal Cakrawala Pendidikan, 2016)
The inter-religious harmony should be done among the pluralistic society like Indonesia. Several ways can be made for building inter-religious harmony. The raising consciousness to appreciate religious freedom from adherents of a religion to others is a key for building this harmony. To make the consciousness grows can be made with several ways, among them is religious study method both by normative-theological approach and critical-empirical approach. The religious education in university, especially in public university, is one of medium can be made to do religious study for building inter-religious harmony. The religious education can be done by exclusive particularistic way for each adherent of a religion for martering his religious principles in depth. For building inter-religious harmony, the religious education will be more effectively if it be done by pluralistic way, by participating all of the students from several adherents of a religion to attend the study of religions. They are given the comprehensive understanding to religions, especially about the equality, until they have consciousness to appreciate another religion with available.